2001
DOI: 10.1088/0953-8984/13/33/105
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in a pyrochlore oxide, Cd2Re2O7

Abstract: We make the first report that a metallic pyrochlore oxide, Cd2Re2O7, exhibits type II superconductivity at 1.1 K. The pyrochlore oxide is known to be a geometrically frustrated system, which includes a tetrahedral network of magnetic ions. A large number of compounds are classified in the family of pyrochlore oxides, and these compounds exhibit a wide variety of physical properties ranging from insulator through semiconductor and from bad metal to good metal. Until now, however, no superconductivity has been r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
131
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(138 citation statements)
references
References 10 publications
6
131
1
Order By: Relevance
“…7 are scaled to the µSR value of λ(1.75 K) at µ 0 H =1 T. It is seen that between 0.6 T and 4.8 T the λ vs H dependence is almost flat. A linear fit of the data in this field range yields a slope η = −0.07 (2), in agreement with the η value obtained from the µSR experiment.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…7 are scaled to the µSR value of λ(1.75 K) at µ 0 H =1 T. It is seen that between 0.6 T and 4.8 T the λ vs H dependence is almost flat. A linear fit of the data in this field range yields a slope η = −0.07 (2), in agreement with the η value obtained from the µSR experiment.…”
supporting
confidence: 86%
“…1,2,3,4,5,6,7,8 However, till now there is no agreement about the nature of superconducting pairing mechanism in these compounds. From the one hand, based on the results of the specific heat, 9 nuclear quadrupole resonance (NQR) 10 and muon-spin rotation (µSR) 11,12 experiments, Cd 2 Re 2 O 7 is suggested to be a weak-coupled isotropic BCS superconductor.…”
Section: Introductionmentioning
confidence: 99%
“…In this Letter, we report polarized Raman investigations of the superconducting oxide Cd 2 Re 2 O 7 [6,7,8], which shows evidence of Goldstone phonon mode behavior. To the best of our knowledge, this is the first observation of a Goldstone optical phonon mode in a crystalline solid.…”
mentioning
confidence: 96%
“…1). Recently, Hanawa et al and the others reported the first superconductor Cd 2 Re 2 O 7 (T c =1 K) in the family of pyrochlore oxides [4,5,6]. The compound exhibits two more phase transitions at T s1 =200 K and T s2 =120 K, where electrical and magnetic properties change dramatically [7,8,9].…”
mentioning
confidence: 99%